2020
DOI: 10.1108/itp-03-2019-0117
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-deprived e-commerce: the efficacy of consumer privacy policies on China's e-commerce websites from a legal perspective

Abstract: PurposeDespite grave public concerns over information privacy and ongoing academic explorations of privacy policy, there is a general lack of understanding toward this issue in the legal context in China, the largest e-commerce market in the world. Departing from the extant literature of general discussion in nature, the authors undertook an exploratory study on the efficacy of e-commerce websites' privacy policies in China from the legal perspective.Design/methodology/approachThe authors drew on a qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 58 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…As a result, the staff need time to conduct supervision and levy taxes, and, consequently, the willingness and desire for cross-border e-business cannot be met. Subsequently, [23,26] highlighted the contemporary issues in the duties management of cross-border e-business transactions; these issues include ensuring adequate oversight of small items, determination of the tax rate to levy on cross-border e-products, and the turnaround time when returning and exchanging commodities [48]. Therefore, adequate measures should to be implemented to adjust the effectiveness of the duties.…”
Section: Efficiency and Supervision Of Custom Clearancementioning
confidence: 99%
“…As a result, the staff need time to conduct supervision and levy taxes, and, consequently, the willingness and desire for cross-border e-business cannot be met. Subsequently, [23,26] highlighted the contemporary issues in the duties management of cross-border e-business transactions; these issues include ensuring adequate oversight of small items, determination of the tax rate to levy on cross-border e-products, and the turnaround time when returning and exchanging commodities [48]. Therefore, adequate measures should to be implemented to adjust the effectiveness of the duties.…”
Section: Efficiency and Supervision Of Custom Clearancementioning
confidence: 99%
“…The questionnaire contains 14 items that represent all the variables assessed in this study. Among those 14 [24]. Furthermore, a 7-Point Likert Scale method was also implemented as the measurement scale to assess the respondents' response toward the questionnaire, in which each respondent could show their response regarding each and every statement included in the questionnaire, which ranges between "1" as strong disagreement and "7" as strong agreement toward the statement.…”
Section: Methodsmentioning
confidence: 99%
“…E-Commerce has been determined and considered as one of the most-developed business sectors in the world. Furthermore, several authors have also suggested and stated that compared to other sectors, such as the automotive, healthcare, and smartphone business, the ecommerce stands out as one of the most promising and highly-developed sectors not only in the world, but also in Asia and Indonesia due to its constantly-increasing growth-rate and the rapid increase of market value of each company within the industry [19] [24]. Moreover, ecommerce has also been classified as one out of ten most promising industries for people or investors to invest their money in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Article 12 of the United Nations Declaration of Human Rights 1948 recognized privacy as a fundamental human right (Combe, 2009; Schöpfel, 2016; Zhu et al , 2020). Article 17 of the International Covenant on Civil and Political Rights states that “no one shall be subjected to arbitrary or unlawful interference with this privacy, family, home or correspondence, nor to unlawful attacks on his honor and reputation” and that “everyone has the right for the legal protection against such interference or attacks.” Article 21 of the Association of Southeast Asian Nation (ASEAN) Human Rights Declaration also explicitly recognized privacy as a human right (Greenleaf, 2011).…”
Section: Literature Review: Legal Aspects Of Personal Datamentioning
confidence: 99%
“…In the context of personal data protection, many empirical studies have investigated many of its aspects. Zhu et al (2020) identified that there is a general distrust among Chinese consumers toward national privacy policies and highlighted that the existing legal enforcement of privacy policies remains largely ineffective despite growing concerns, affecting their perceptions and behaviors in buying. Their paper reveals that the existing Chinese legislation, due to its limited recognition and influence among consumers, is currently not capable to fully build their confidence in the effectiveness of websites’ privacy policies and protection measures (Zhu et al , 2020).…”
Section: Introductionmentioning
confidence: 99%